FOUNDRY – PULSE METHOD OF ARTICLES PRODUCTION FROM ALLOY ON THE BASIS OF THE TITANIUM- ALUMINIUM - A. F. Ilyuschenko; G. V. Kupchenko; A. R. Luchenok; A. A. Luchenok; N. V. Kirshina; O. A. Poko; A. V. Mayonov (Литьë и металлургия)
Consider the process of obtaining an addition alloy products from alloys of titanium-aluninum systems, which includes metallutgical and pulse processing of powder materials.